Shariah Status, Board Gender Diversity and the Location and Extent of Corporate Social Responsibility Reporting. (Global Business Management Review (GBMR), 2022)
The disclosure of Corporate Social Responsibility (CSR) has been mandated as a requirement in Malaysian firms’ annual reports starting from the year 2007. However, the framework provided by Bursa Malaysia does not indicate specific location for disclosure. As a result, a pilot study conducted on the 2009 annual reports revealed that although all the firms disclose CSR information in the annual reports, it is also found that there are two different locations for reporting: 63% of the sampled companies have a stand-alone segment in annual reports, while the remaining 37% disclose their CSR activities as part of the Chairman’s Statement, Corporate Governance Statement, Manager’s Report, Operations Review segment, Additional Compliance Information segment and Other Information segment. Previous studies indicate that Shariah-compliant firms are expected to be socially responsible and to provide full disclosure while the presence of women on the board of directors is strongly linked to philanthropic activities. Based on these insights, we predict that Shariah-compliant firms and firms having board gender diversity will have greater CSR activities and disclosure via stand-alone CSR reports. Therefore, the aim of this study is to see whether Shariah status and the presence of women on the board of directors and having women as CEO are associated to the location and extent of CSR reporting. The 2009 annual reports of 54 Malaysian firms will be examined and the extent of CSR will be measured by the number of words, sentences and pages. The result of this study will provide insights on the relevance of Shariah status, having women on the board of directors and as CEO with respect to CSR reporting